Co-operating of organs of internal affairs with citizens, non-state forming in providing of public peace and public safety (Journal of actual problems of jurisprudence, 2019)
The article is sanctifi ed to the issues of the day of cooperation of organs of internal affairs in providing of public peace and publicsafety in Republic of Kazakhstan, with citizens and non-state forming of public law enforcement. An author is consider the problemaspects of theory and practice of perfection of activity of law enforcement authorities in providing of public peace and public safety.